Emergency Kit Vending Machine Using RFID - Hidayat Halim; Hikma Shabani (Progress in Engineering Application and Technology, 2022)
The project is to build up a computerized emergency kit vending machine using RFID to serve people at any time and wherever they are in specific territories for example, expressways, provincial regions and other places with less drug stores and pharmacies .This machine tend to give the required medication as per his sickness. It is a sort of automated medication stockpiling framework which can be handily gotten to by the individuals in crisis without moving toward any drug stores or pharmacies. The aims of this project are to design and develop a low-cost prototype of emergency kit vending machine using RFID that will help to decrease the time taken to get medicine or medical items and to make it easier for people to find medications. The main component is Arduino Uno as the processor of the project system. Then, RFID reader used as the card reader and allows to access the medicine vending machine. Next, are keypad and LCD used to display the number of chamber that user has been selected by press the keypad. Last but not least, the servo motor used to rotate and push out the item. The system is runs according to the program source code written in the Arduino IDE. At the end of the project, the prototype of the emergency kit vending machine is designed, which proves that the system from the code sources can be functioning according to user access card